Maximum Phonation Time in People with Obesity Not Submitted or Submitted to Bariatric Surgery. (31st December 2019) - Fonseca, Ana Luara Ferreura; Salgado, Wilson; Dantas, Roberto Oliveira
Abstract : Background . Our aim in this investigation was to evaluate maximum phonation time in people with obesity not submitted to surgery and in people with obesity submitted to bariatric surgery and compare it with maximum phonation time of healthy volunteers. The hypothesis was that the reduced maximum phonation time in people with obesity would be corrected after surgery due to weight loss. Method . Maximum phonation time was evaluated in 52 class III patients (Group A), 62 class III patients who were treated by surgery 3 to 115 months before (Group B), 20 controls (Group C), and 15 class III patients whose maximum phonation time was evaluated before and two to six months after surgery (Group D). Maximum phonation time was measured in the sitting position with the vowels /A/, /I/, and /U/. Results . Maximal phonation time was shorter in groups A and B compared with that of controls. There was an increase in maximal phonation time after surgery (Group B); however, the difference was not significant when compared with that in group A. In group D, maximal phonation time for /A/ increased after the surgery. In group A, there was a negative correlation between maximal phonation time and weight or body mass index and a positive correlation between maximal phonation time and height. In group B, there was an almost significant positive relation between percentage of weight loss and maximal phonation time for /A/ (p = 0.08 ) and /I/ (p = 0.07 ). Mean values of spirometry testing (FEV1, FVC, and FEV1 /FVC) in people with obesity (groups A and B), expressed as percentage of the predicted value, were within the normal range. Conclusion . Compared with healthy controls, maximal phonation time is shorter in people with obesity, with a tendency to increase after bariatric surgery, as a possible consequence of weight loss.